1993
DOI: 10.1111/j.1464-410x.1993.tb16066.x
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Pain following Intravesical Capsaicin in Patients with Hypersensitive Disorders of the Lower Urinary Tract

Abstract: We have extended our earlier observations on pain relief produced by intravesical instillation of capsaicin (10 microM in saline) in patients with hypersensitive disorders of the lower urinary tract. Patients in group A (n = 15) received intravesical capsaicin on days 0, 14 and 28: on each occasion the drug produced a warm or burning sensation, reduction in bladder capacity and a delayed, transient improvement or disappearance of symptoms. Patients in group B (n = 5) received intravesical capsaicin (10 microM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…We therefore sought to explore the nature of the afferent fibers responsible for this effect. The TRPV1 agonist, capsaicin (trans-8-methyl-N-vanilly-6-nonenamide), has been used to desensitize a subpopulation of small-diameter, unmyelinated C-fiber afferents that innervate the bladder, leav- ing the other afferents unaffected (Barbanti et al, 1993;de Groat, 1993). In animals pretreated with capsaicin (100 mg/kg s.c.), 4 days before the experiment, there was no significant change in bladder contraction amplitude or intercontraction interval in the cystometrograms of rats perfused with saline as previously reported (Cheng et al, 1999).…”
Section: ␣-Pdd Augments Bladder Contraction Via a Capsaicin-insensitmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore sought to explore the nature of the afferent fibers responsible for this effect. The TRPV1 agonist, capsaicin (trans-8-methyl-N-vanilly-6-nonenamide), has been used to desensitize a subpopulation of small-diameter, unmyelinated C-fiber afferents that innervate the bladder, leav- ing the other afferents unaffected (Barbanti et al, 1993;de Groat, 1993). In animals pretreated with capsaicin (100 mg/kg s.c.), 4 days before the experiment, there was no significant change in bladder contraction amplitude or intercontraction interval in the cystometrograms of rats perfused with saline as previously reported (Cheng et al, 1999).…”
Section: ␣-Pdd Augments Bladder Contraction Via a Capsaicin-insensitmentioning
confidence: 99%
“…Studies in humans and laboratory animals have demonstrated the importance of capsaicin-sensitive neurons in certain forms of pathological bladder hyperreactivity (Abelli et al, 1988;Chancellor and de Groat, 1999). Accordingly, patients suffering from neurogenic bladder hyperreactivity experience relief from both urinary frequency and urgency after intravesical desensitization with TRPV1 agonists (Barbanti et al, 1993;Chancellor and de Groat, 1999;Fowler, 2000). Previously, we reported that TRPV1 is expressed not only in bladder sensory neurons but also in urothelial cells (Birder et al, 2001).…”
mentioning
confidence: 99%
“…Only two were randomized placebo-controlled trials [10, 11]. The other eight were open noncontrolled studies [2, 3, 4, 5, 6, 7, 8, 9]. Follow-up lasted approximately 1 month in three studies, 6 months in three, and over 1 year in five.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was confirmed by subsequent clinical studies. Eight open studies [2, 3, 4, 5, 6, 7, 8, 9]and two randomized placebo-controlled trials [10, 11]have shown the efficacy of intravesical instillation of capsaicin against neurogenic bladder disorders including detrusor hyperreflexia, hypersensitive disorders of the lower urinary tract and severe bladder pain. However, the interpretation of these studies is hampered by the lack of consensus regarding the parameters used to evaluate the tolerance and efficacy of instillations and the diversity of therapeutic protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit lasted for 3-4 months, when the instillations were repeated In 1993, Barbanti et al [34] reported the relief of pain using intravesical capsaicin in the same doses as had using 2 mmol/L of capsaicin. Over a 5-year period, the beneficial eCect of these repeated instillations was susbeen used by Maggi et al [33] in patients with hypersensitive bladder disorders.…”
Section: Topical Capsaicin For the Treatment Of Painful Conditionsmentioning
confidence: 99%